La mode française : vecteur d'influence aux États-Unis de l'après-guerre à l'orée des années 1960 - Dubé-Senécal, Vincent (Université de Montréal, 2019)
This thesis is a survey of a rarely studied field of international relations. It is interested in the role of women’s sartorial fashion within the Franco-American postwar relations between 1946 and 1960. The analysis takes on the French perspective through the prism of the public authorities and diplomatic bodies, Parisian couturiers, and textile manufacturers. This orientation highlights the two fields on which these actors wish to see manifest an influence of fashion in the United States, namely commercial and prestige propaganda. In their perspective, these two forms of propaganda can be implemented either through indirect actions (press coverage of their fashion shows) or direct actions (shows organized to promote specific products or French production as a whole). The analysis is then completed by integrating the perspective of American fashion professionals (specialized press, manufacturers and retailers) and that of the American diplomatic bodies in France, and the study of customs statistics in order to evaluate, from the viewpoint of these historical actors, the degree of success of fashion as an instrument of French influence in the United States in regard of the initial French expectations. The research question answered by this thesis is: How important is fashion as an instrument of French influence in the United States after the Second World War? In order to answer it, the analyses procedes in three steps. On the one hand, the intersection of the historical contexts of fashion and Franco-American relations highlights the importance of the advent of the American superpower. This requires the French to adapt in terms of their production methods and their relationship to the American perspective of liberal and democratic modernity. On the other hand, the research was based on a chronological approach distinguishing between the 1946-51 and 1952-60 periods. The first one precedes the state intervention in favor of the Parisian couturiers and the second one is dominated by the state-sponsored Aid to Parisian couture. The thesis shows that the commercial influence of Parisian fashion in the United States did not materialize contrary to the couturiers’ claims and to the textile industrialists’ expectations. However, with respect to its influence through prestige propaganda, the situation is quite different. Long regarded as an ersatz to the commercial purpose of propaganda by the state – with the exception of the French diplomatic bodies that particularly appreciate its prestige purpose –, from 1957, France’s “rayonnement” through the dissemination of fashion ideas becomes key to French leaders. From then on, its role is to take advantage of the craving for Parisian fashion ideas to ensure a French presence – beyond fashion – in the American market: a mass market otherwise difficult to penetrate, being the largest in the world.
Keywords: Commercial relations; Fashion; France; Haute couture; History - European / Histoire - Européenne (UMI : 0335); Influence transnationale; International relations; Mode; Propaganda; Propagande; Relations commerciales; Relations internationales; Transnational influence; United States; États-Unis